LEARNING THE NONFORMAL EDUCATION THROUGH RESEARCH METHODOLOGY: A LITERATURE REVIEW - Muhammad Alim Hafidz; Elihami Elihami; Humairah Izzatun nisa (Universitas Muhammadiyah Enrekang, 2021)
The taking up of a “educative” mantle has proven to be a complicated endeavor for museums, replete with numerous unknown and/or misinterpreted aspects. Of the great diversity of educational options museums give its adult clients and personnel, the bulk fit into one or two learning categories: either they are nonformal or informal. This literature review intends to examine both conceptual and empirical research that explores nonformal and informal contexts of learning within museum settings in order to create a greater understanding of adult nonformal and informal learning in museums. Dissertation Abstracts, Web of Science, ERIC, and ProQuest Direct were among the academic search engines we used.